On Reliability of Renewable Binary Elements’ System - Andronov, A. M.; Dalinger, I. M. (Automatic control and computer sciences, 2018)
In this research, a system with renewable elements is considered. A lifetime and a renewal time have exponential distribution, which differs for different components. The renew is performed by s servers. The order of the failed elements’ service is determined by the priority of the elements. An absolute discipline is used. The system works if elements’ states belong to fixed set. Consideration is given to transient and stationary regimes. The system reliability function is studied.